Hubungan Mobilisasi Dini dengan Penyembuhan Luka Perineum pada Ibu Postpartum - Dwi Retno Handayani; Fadhila Arienda Humaira; Riska Reviana (Pusat Riset dan Inovasi Nasional, 2024)
Childbirth often results in perineal tears, particularly in first-time deliveries, and can also occur in subsequent births. Improper perineal care can create a moist environment due to lochia, promoting bacterial growth and increasing the risk of infection, which may delay wound healing. Complications of perineal tears include bleeding, infection, and dyspareunia. This study aimed to analyze the relationship between early mobilization and perineal wound healing in postpartum mothers in 2020. The research used an analytical survey with a cross-sectional approach, involving 30 postpartum patients at PMB Bidan Ai Duriah through total sampling. Data collection was conducted using observation sheets, and analysis was performed with the chi-square test at a 95% significance level (p < 0.05). Results indicated that most postpartum mothers (20 respondents) experienced good perineal wound healing with early mobilization. The study concludes that early mobilization plays a significant role in promoting perineal wound healing in postpartum mothers.